The Diffusion of Telehealth in Rural American Indian Communities: A Retrospective Survey of Key Stakeholders - Brooks, Elizabeth (Mary Ann Liebert, Inc., 2012)
Objective: Mental health issues are a serious concern for many American Indian Veterans, especially for post-traumatic stress disorder and related psychiatric conditions. Yet, acquiring mental health treatment can be a challenge in Native communities where specialized services are largely unavailable. Consequently, telehealth is increasingly being suggested as a way to expand healthcare access on or near reservation lands. In this study, we wanted to understand the factors affecting the diffusion of telehealth clinics that provided mental health care to rural, American Indian Veterans. Materials and Methods: We surveyed 39 key personnel and stakeholders who were involved in the decision-making process, technological infrastructure, and implementation of three clinics. Using Roger Everett's Diffusion Theory as a framework, we gathered information about specific tasks, factors hindering progress, and personal reactions to telehealth both before and after implementation. Results: Many participants expressed initial concerns about using telehealth; however, most became positive over time. Factors that influenced participants' viewpoint largely included patient and staff feedback and witnessing the fulfillment of a community health need. The use of outside information to support the implementation of the clinics and personal champions also showed considerable influence in the clinics' success. Conclusion: The findings presented here address critical gaps in our understanding of telehealth diffusion and inform research strategies regarding the cultural issues and outcomes related to telemental health services. Information contained in this report serves as a long overdue guide for developing telemental health programs and policies among American Indians, specifically, and rural populations in general.